Production of recombinant H1 parvovirus stocks devoid of replication-competent viruses - Brown, Caroline S.; Rommelaere, Jean; Dinsart, Christiane (Human gene therapy, 2002)
Vector and helper plasmids for the production of recombinant H1 (rH1) parvovirus, an oncolytic virus and candidate vector for cancer gene therapy, were constructed with the aim of reducing the contamination of these preparations with replication-competent viruses (RCV). Split-helper plasmids were constructed by manipulating the splicing signals for the capsid proteins such that VP1 and VP2 were expressed from separate plasmids. H1 vectors with similarly mutated splice sites were packaged, using the split-helper plasmids, and the resulting recombinant H1 viruses were completely free of RCV because the generation of recombinants expressing both capsid proteins was prevented. Vector yields of rH1 produced with split-helper plasmids in combination with splice site-modified vectors were similar (in the range of 107 replication units/ml) to yields of rH1 produced with the standard vector/helper pair, in which case significant levels of RCV were generated (104-105 plaque-forming units/ml). To assess the functionality of this approach in vivo, rH1 was produced that contained the human interleukin 2 (IL-2) transgene and that was devoid of RCV. This IL-2-carrying rH1 vector expressed IL-2 efficiently in human tumor cells (HeLa) in vitro and generated antitumor responses in nude mice xenografted with HeLa cells that had been infected ex vivo with this virus. These results should allow the large-scale production of recombinant oncotropic parvoviruses and their assessment for the gene therapy of cancer in a clinical setting.